Soluble Human Leukocyte Antigen Molecules Detected in Orofacial Cleft Patients: A Case-Control Study - Regina Purnama Dewi Iskandar; Alida; Ari Triwardhani; Ida Bagus Narmada; Faizah Hanum; Arief Haryo Kusumo; Chairul Anwar Nidom; Sri Agus Sudjarwo (Association of Support to Oral Health Research (APESB), 2022)
Objective: To compare soluble HLA-C and HLA-DR molecules present in the plasma of orofacial cleft and non-orofacial cleft populations. Material and Methods: Orofacial cleft patients were recruited using an accidental sampling approach (n=15). Peripheral blood was collected from the participants and processed for Enzyme Linked Immunosorbent Assay (ELISA) against HLA-C and HLA-DR with specific antibodies. The absorbance was calculated utilizing ELISA reader. Data were statistically analyzed using an independent t-test to compare the disease and control groups. Results: The levels of soluble HLA-C and HLA-DR were significantly higher in the diseased group compared to the control group (p<0.05). Conclusion: The role of HLA molecules in non-communicable disease and congenital anomalies, particularly orofacial cleft, remains speculative despite the positive results of this study and  those  of previous investigations. It suggests that the variables examined may affect specific pathways involved in the pathogenesis of orofacial cleft, and predispose the individuals concerned to the oral cleft.